Evaluating the effect of natural, industrial juices and beverage on orthodontic bonding composite (in-vitro study) - Rusal S Ahmed; Alan I Saleem (College of Dentistry/ University of Baghdad, 2023)
Background: Dental erosion is a common oral condition which results due to consumption of high caloric and low pH acidic food such as carbonated drinks and fruit juices. It is expected that these food types can cause irreversible damage to dental hard tissues and early deterioration of the dental restorations. So, this study aimed to evaluate and compare the erosive potential effects of orange fruit juice and Miranda orange drink on the microhardness of an orthodontic composite material. Materials and methods: Thirty discs with a thickness of 2 mm and a diameter of 10 mm were prepared from orthodontic bonding composite. The prepared discs were equally divided into three groups (n=10). Microhardness analysis was carried out both prior to and subsequent to immersion cycles. The microhardness of the specimens underwent evaluation subsequent to immersion in the beverages for durations of 6 hours (equivalent to one day) and 42 hours (equivalent to seven days). Microhardness measurements at baseline, one day, and one week were performed utilizing the Vickers microhardness testing. Statistical analyses were carried out using repeated measure one way ANOVA test and Bonferroni post-hoc test with a level of significant p< 0.05. Results: The micro hardness of composite exposed to the selected soft drinks was significantly decreased (p< 0.05). Conclusions: Natural, industrial orange juices and Miranda can affect the micro hardness of composite. The beverage effect on the orthodontic composite based on the type of juice and the exposure time to these beverages.